A Novel Approach to Kinetic Equations of Fractional Order Pertaining to Hyper-Bessel Function - Komal Prasad Sharma; Alok Bhargava; Annu Jangra (Utilitas Mathematica, 2025)
Special functions included in fractional kinetic equations have been shown to be helpful in the explanation and resolution of numerous important mathematical and mathematical physics issues. Because arbitrary-order kinetic equations are so important, the goal of this study is to use the Sumudu Transform technique to solve a new fractional-order kinetic equation involving the Hyper Bessel function with their fractional derivatives. MATLAB-generated graphical representations used in our analysis to demonstrate the behavior of these solutions under various parametric values. The outcomes of the study are highly flexible and may lead to both confirmed and maybe undiscovered research findings in this field.